Changes in framing of pornography in a Malaysian newspaper from 2017 to 2024. - Pung, Wun Chiew; Ting, Su Hie (Asian Scholars Network (ASNet), 2024)
This study investigates changes in framing of pornography in a Malaysian newspaper from 2017 to 2024. The specific aspects examined are (1) the prevalence of episodic and thematic frames, and (2) changes in frames on pornography over time. A search using the words “porn” and “pornography” was conducted in the online portal of New Straits Time, and 24 articles were identified. Content analysis was conducted based on Goffman’s (1974) Framing Theory. The results show that most news articles on pornography were reported using the episodic frames throughout the eight-year period. However, there has been an increase in the use of thematic frames to situate incidents in the broader societal trends. This reflects a shift toward viewing pornography as a systemic issue. As for frame dimensions, the morality frame remains dominant. However, news articles on pornography in recent years show a concern for public health and safety, and technological challenges and responsibility. The findings indicate that Malaysian news media could be taking on a more active role in educating the public about the harms of pornography and the need for coordinated efforts to monitor activities and protect the vulnerable populations.